THE MARKET DAY ACTIVITIES IN FOSTERING INDEPENDENCE AND CREATIVITY OF ELEMENTARY SCHOOL STUDENTS - Farhati Salsabila; Arief Cahyo Utomo (Universitas Islam Negeri Mataram, 2025)
This study aims to describe how Market Day activities foster the character of independence and creativity in students at SDIT Mutiara Insan Sukoharjo. This study uses a qualitative approach with descriptive methods and phenomenological design. Data was collected through participatory observation, in-depth interviews, and document analysis, then analysed using the Miles and Huberman model, which included data reduction, data presentation, and conclusions drawn. The results of the study show that Market Day activities are carried out routinely and in a structured manner. All students from the lower to the upper classes participated and took turns according to the predetermined schedule. Through this activity, students are trained to design products, determine prices, serve buyers, determine sales strategies and complete transactions independently. Students also show creativity in choosing promotional strategies, overcoming challenges, and making sales posters. Supporting factors for the success of this activity include students' enthusiasm and problem-solving skills, school support, teachers' roles, and parental involvement. However, there are also obstacles such as limited numeracy skills, differences in confidence levels between students and a lack of interest in some products sold by students. Overall, Market Day at this school proved to be an effective means to instil entrepreneurial character values, especially independence and creativity, in a fun and meaningful learning atmosphere.